Сomponents «Tyn/Plit» (the Fence/Hedge) in the Phrasemes of Dialectal Language (Linguostylistic Studies, 2017)
The article highlights the symbolic content and spatial distribution of the phrasemes with components «tyn / plit»,  which is one of the main traditional symbols of the Ukrainian culture. The author analyzes the issue of the phrasemes on the material from lexicographical sources and the examples from dialectal texts of three dialects of the Ukrainian language, reveals their semantic varieties and systematizes them. The emphasis is laid on certain areas of their use, possible accompanying words, regularity of the phenomena. The study seeks out to prove that culture information of a nation is displayed/ revealed in different contexts, and especially in phraseology. The border between «the own» and «someone else’s» space is the anthropological subjective center in the consciousness of any ethnos. The author draws conclusions that verbalization of the semantic meaning of the phrazeologizms with components «tyn / plit» is actualized in two dimensions – to perform certain actions near the fence and to carry out  some kinds of work with the fence.
Keywords: phraseological unit; component; dialectal language; dialect